Habituation of Green Education Based on Islamic Values: Instilling Environmental Ethics from an Early Age - Khumairo, Siti; Chasanah, Iflahatul; Salsabila, Annida Azka Putri (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
his study examines the implementation of environmental education from an early age at SDIT Al Akbar through simple habituation activities rooted in Islamic values. The research aims to identify how daily practices can shape students’ environmental awareness and moral responsibility. A qualitative descriptive method was employed, with data collected through observation, interviews, and documentation. The findings reveal that routine activities such as watering plants, maintaining classroom cleanliness, and using water wisely have become ingrained habits among students. These practices not only foster environmental responsibility but also reflect Islamic teachings on stewardship (amanah) and moderation (israf). Lessons in Aqidah Akhlak, Fiqh, and Science further reinforce students’ understanding of caring for nature as part of faith and moral conduct. Teachers and parents play crucial roles as role models and facilitators, ensuring consistency between school and home environments. Despite several challenges, such as limited facilities and varying levels of student awareness, this habituation model has proven effective in building a culture of environmental care from an early age. The study contributes to the development of integrative environmental education that combines ecological awareness with Islamic moral values. It also provides a practical framework for other Islamic schools seeking to implement meaningful and sustainable environmental learning practices.